An intravascular papillary endothelial hyperplasia of the hand radiologically mimicking a hemangiopericytoma: A case report and literature review. (9th January 2018) - Pesce, Vito; Bizzoca, Davide; Notarnicola, Angela; Piazzolla, Andrea; Vicenti, Giovanni; Cimmino, Antonietta; Fortarezza, Francesco; Maccagnano, Giuseppe; Solarino, Giuseppe; Moretti, Biagio
Intravascular papillary endothelial hyperplasia is a rare benign vascular lesion of the skin and subcutaneous tissues, characterized by a reactive proliferation of endothelial cells that can present de novo in normal blood vessels (primary intravascular papillary endothelial hyperplasia), but it can also develop from a pre-existing vascular process (type II intravascular papillary endothelial hyperplasia), or it can arise in an extravascular location from a post-traumatic haematoma. The differential diagnosis between intravascular papillary endothelial hyperplasia and malignant vascular tumours can be challenging, due to the lacking of a specific radiologic description. We present a case of intravascular papillary endothelial hyperplasia of the hand radiologically mimicking a hemangiopericytoma.